Energy, exergy and environmental analyses of conventional, steam and CO2-enhanced rice straw gasification - Parvez, A.M.; Mujtaba, I.M.; Wu, T. (Elsevier, 2016)
In this study, air, steam and CO2-enhanced gasification of rice straw was simulated using Aspen Plus™ and compared in terms of their energy, exergy and environmental impacts. It was found that the addition of CO2 had less impact on syngas yield compared with gasification temperature. At lower CO2/Biomass mass ratios (<0.25), CO2-enhanced gasification showed a lower GSE (gasification system efficiency) than conventional gasification, which was below 22.1%. However at higher CO2/Biomass ratios, CO2-enhanced gasification demonstrated higher GSE than conventional gasification. The GSE of CO2-enhanced gasification continued to increase to 58.8% when CO2/Biomass ratio was raised to 0.87. It was also found that chemical exergy was 2.05–4.85 times higher than physical exergy. The syngas exergy increased with CO2 addition, which was mainly due to the increase in physical exergy. The maximum exergy efficiency occurred in the temperature range of 800 °C–900 °C. For CO2-enhanced gasification, exergy efficiency was found to be more sensitive to temperature than CO2/Biomass ratios. In addition, the preliminary environmental analysis showed that CO2-enhanced gasification resulted in significant environmental benefits compared with steam gasification. However novel assessment methodologies are still needed to better evaluate the advantages of CO2 utilization.